The Corpus of Russian Translations of Social and Political Works of the Eighteenth Century - Sergey Polskoy; Vladislav Rjéoutski (Вивліоѳика, 2021)
The project that has been carried out at the German Historical Institute in Moscow since 2016 continues the engagement of the Institute in the development of the history of concepts in Russia. The previous project, “The History of Concepts and Historical Semantics,” which was led by Ingrid Schierle and Denis Sdvizkov (both research fellows at the German Historical Institute in Moscow at the time), was undertaken between 2008-2014. It consisted of a series of conferences and resulted in several publications; namely, two volumes devoted to the history of key concepts in the Russian imperial period. However, the main focus of the current project is on translation as a laboratory of the Russian language of “civil sciences.” The project is being coordinated by Sergey Polskoy (Higher School of Economics, Moscow) and Vladislav Rjéoutski (German Historical Institute in Moscow). In addition, the editorial work on the database is being carried out by Evgenii Kushkov (Higher School of Economics, Moscow), with Vadim Popov (GHI Moscow) also being responsible for statistics and the visualization of the results of the project.